Asthma: pathogenesis and novel drugs for treatment. (24th November 2014) - Olin, J Tod; Wechsler, Michael E
Abstract : Asthma affects almost 20 million people in the United States and more than 300 million people worldwide. Of these, 10-15% have severe asthma, which is refractory to commonly available drugs. New drugs are needed because those that are currently available cannot control symptoms and exacerbations in all patients and can cause adverse reactions. In the past 10 years, there have been substantial advances in the understanding of asthma genetics, airway biology, and immune cell signaling. These advances have led to the development of small molecule therapeutics and biologic agents that may improve asthma care in the future. Several new classes of asthma drugs—including ultra long acting β agonists and modulators of the interleukin 4 (IL-4), IL-5, IL-13, and IL-17 pathways—have been evaluated in randomized controlled trials. Other new drug classes—including dissociated corticosteroids, CXC chemokine receptor 2 antagonists, toll-like receptor 9 agonists, and tyrosine kinase inhibitors—remain in earlier phases of development. Despite some preliminary efficacy data, there is insufficient evidence to make strong recommendations about the use of these newer agents. Future research on the clinical efficacy of these biologic agents, the effect of newer agents on severe asthma in pediatric patients, and the biology of non-eosinophilic and corticosteroid resistant asthma is needed to reduce the morbidity of asthma worldwide.